2012
DOI: 10.1152/ajprenal.00543.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine elevation and transaminitis after laparoscopic donor nephrectomy

Abstract: Yap S, Park SW, Egan B, Lee HT. Cytokine elevation and transaminitis after laparoscopic donor nephrectomy. Am J Physiol Renal Physiol 302: F1104 -F1111, 2012. First published January 18, 2012 doi:10.1152/ajprenal.00543.2011.-Acute kidney injury frequently occurs in the critically ill and often progresses into multiorgan dysfunction syndrome, resulting in high mortality. We previously showed that nephrectomized mice had increased interleukin (IL)-6 and tumor necrosis factor (TNF)-␣ that directly contributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…Yap 24 did not demonstrate an elevated uNGAL before 24hrs in their study of donor nephrectomy patients, though the only previous sample was at 5hrs post op. In that study, as in ours, mean NGAL did not reach AKI levels (150ng/ml) even at 24 hrs.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Yap 24 did not demonstrate an elevated uNGAL before 24hrs in their study of donor nephrectomy patients, though the only previous sample was at 5hrs post op. In that study, as in ours, mean NGAL did not reach AKI levels (150ng/ml) even at 24 hrs.…”
Section: Discussionmentioning
confidence: 86%
“…The high rate of AKI in the RN group, as calculated by AKIN criteria (which allows for a rise in sCr within 48 hours after injury), has been seen in up to 75% of patients in other studies. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are very small number of human studies in the literature addressing this important topic. One study investigated the effect of pneumoperitoneum after laparoscopic donor nephrectomy [8]. However, donor patients were healthy and rigorously screened for preexisting comorbidities and the patients were not compared to open procedure.…”
Section: Samples Collectionmentioning
confidence: 99%
“…Therefore, many studies reporting changes in NGAL with acute kidney injury, kidney surgery, or renal ischaemia–reperfusion injury have analysed urinary NGAL (uNGAL) rather than (or in addition to) sNGAL . Several observational studies have evaluated uNGAL in kidney donors, but none have definitively reported how uNGAL relates to renal function of the living kidney donor . Therefore, we conducted the present prospective study to assess clinical implications of uNGAL in living kidney donation.…”
Section: Introductionmentioning
confidence: 99%